2007
DOI: 10.3208/jgs.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Soil tank test on seepage and failure behaviors of Shirasu slope during rainfall

Abstract: The changes in climate all over the world have brought various natural disasters such as flood, drought and so on. In Japan various types of slope failures due to rainfall often occur in the rainy season. Therefore Kitamura et al. have proposed a prevention system of slope failures due to rainfall. In this paper, the soil tank tests are carried out in order to analyze the mechanism of slope failure due to rainfall. The pore-water pressure in the soil is measured by the tensiometers and pore-water pressure sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Interestingly, the formation of a typical sheared zone in the slope is properly predicted, in which the shear strain is localized over a narrow zone. The calculated sheared zones by the four coupled models all start to form at the toe of slope after about 6 h of infiltration and then propagate toward the slope crest, which are in good agreement with the experimental observations [83]. The propagation of the sheared zone is driven by the rain infiltration.…”
Section: Computational Modelsupporting
confidence: 83%
“…Interestingly, the formation of a typical sheared zone in the slope is properly predicted, in which the shear strain is localized over a narrow zone. The calculated sheared zones by the four coupled models all start to form at the toe of slope after about 6 h of infiltration and then propagate toward the slope crest, which are in good agreement with the experimental observations [83]. The propagation of the sheared zone is driven by the rain infiltration.…”
Section: Computational Modelsupporting
confidence: 83%
“…Recently, research on the failure mechanisms in unsaturated conditions as well as those under saturation conditions have been investigated and have been reported (e.g., Olivares et al [ [6], and Kitamura et al [7]). In particular, Yagi et al [5] indicated the importance of the amount of limited rainfall and proposed a prediction method of failure based on field and experimental data for volcanic slopes.…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%